Threats in context : identify, analyze, anticipate - Perois, Jean (Boca Raton : CRC Press, 2023)
"Threats in Context: Identify, Analyze, Anticipate begins with the premise that a risk assessment is relevant primarily-and hinges upon-the correct evaluation of the threat. According to the author, all the other stages of the risk evaluation are, in fact, dependent on getting the understanding and measurement of the threat right"--
An abridged history of threats from the late 60s to today: a retrospective -- Is our world under threat? -- The globalization of threat -- The Securitization of Threats -- The quest for a method -- Anticipating the threat: Introduction to forecasting principles and techniques.
Keywords: Risk assessment; Risk management; Threats; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management